(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Brand awareness, as one of the fundamental dimensions of brand equity, is often considered to be a prerequisite of consumers’ buying decision, as it represents the main factor for including a brand in the consideration set. Brand awareness can also influence consumers’ perceived risk assessment and their confidence in the purchase decision, due to familiarity with the brand and its characteristics. It be studied into two parts – Brand recall and Brand recognition. These two parts directly or indirectly effect the consumer’s buying decision. The purpose of this paper is to elaborate the relation between awareness of a brand and the intention of consumer of buying that brand.